Charge‐Compensation in a Displacement Mg2+ Storage Cathode through Polyselenide‐Mediated Anion Redox. Issue 29 (18th May 2022) - Qu, Xuelian; Du, Aobing; Wang, Tao; Kong, Qingyu; Chen, Guodong; Zhang, Zhonghua; Zhao, Jingwen; Liu, Xin; Zhou, Xinhong; Dong, Shanmu; Cui, Guanglei
Abstract: Chalcogenides have been viewed as important conversion‐type Mg 2+ ‐storage cathodes to fulfill the high volumetric energy density promise of magnesium (Mg) batteries. However, the low initial Columbic efficiency and the rapid capacity degradation remain challenges for the chalcogenide cathodes, as the clear Mg 2+ ‐storage mechanism has yet to be clarified. Herein, we illustrate that the charge storage mechanism of the Cu2− x Se cathode is a reversible displacement reaction along with a polyselenide (PSe) mediated solution process of anion‐compensation. The unique anion redox improves charge storage, while the dissolution of PSe also leads to performance degradation. To address this issue, we introduce Mo6 S8 into the Cu2− x Se cathode to immobilize PSe, which significantly improves performance, especially the reversible capacity (from 140 mAh g −1 to 220 mAh g −1 ). This work provides inspiration for the modification of the Mg 2+ ‐storage cathode, which is a milestone for high‐performance Mg batteries. Abstract : The Mg 2+ ‐storage mechanism underlying Cu2− x Se, a typical chalcogenide cathode, is a displacement reaction with anionic charge compensation, which is simultaneously accompanied by a polyselenide‐mediated dissolution process. The addition of Mo6 S8 reduces the irreversible capacity and improves the electrochemical performance.